Pengaruh Pertumbuhan Ekonomi, Jumlah Penduduk, Pendidikan Terhadap Pengangguran Terdidik di Jawa Timur - Safitri, Ranti; Endang, Endang (Universitas Batanghari Jambi, 2024)
Unemployment is a phenomenon that can have an impact on a country's economy and cause national income to decrease. This results in decreased public consumption and decreased demand for manufactured goods. The aim of this research is to determine the effect of economic growth, population, and education level on educated unemployment in East Java. This research uses multiple linear regression analysis using the Eviews 10 application. Quantitative research method using secondary data from the Central Statistics Agency (BPS). Based on the research results, economic growth has a negative and significant influence on educated unemployment in East Java. The population has a positive influence and has a significant impact on educated unemployment in East Java. Education level has a positive and significant influence on educated unemployment in East Java.